1996
DOI: 10.1002/(sici)1099-0518(199610)34:14<2841::aid-pola1>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility of poly(ethylene terephthalate)/poly(ethylene 2,6-naphthalate) blends by transesterification

Abstract: The effects of transesterification on the miscibility of poly(ethylene terephthalate)/poly(ethylene 2,6‐naphthalate) were studied. Blends were obtained by solution precipitation at room temperature to avoid transesterification during blend preparation. The physical blends and transesterified products were analyzed by wide‐angle x‐ray scattering, differential scanning calorimetry, and nuclear magnetic resonance spectroscopy. It was found that the physical blends are immiscible and when the extent of transesteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 0 publications
1
46
1
1
Order By: Relevance
“…It is well known that the transesterification reaction readily occurs when polyesters are blended near and above their melting points [16 -21,38]. Stewart et al [16] and Ihm et al [18] reported that this reaction was dependent on the blending time and temperature while the blend composition and the residual polyester catalysts had no significant effect on the reaction. In our preliminary experiments, all the SAED patterns, which were obtained from the uniaxially oriented thin films of PET/PEN blends (PET/PEN ¼ 80/20, 50/50 and 20/80) prepared by applying the shear strain after keeping them in their molten state for 5 min, showed no crystalline reflections, in other words, 5 min is long enough for the transesterification reaction to occur, and accordingly in the resulting uniaxially oriented thin films of PET/PEN blends any crystalline structure was not formed.…”
Section: Resultsmentioning
confidence: 97%
“…It is well known that the transesterification reaction readily occurs when polyesters are blended near and above their melting points [16 -21,38]. Stewart et al [16] and Ihm et al [18] reported that this reaction was dependent on the blending time and temperature while the blend composition and the residual polyester catalysts had no significant effect on the reaction. In our preliminary experiments, all the SAED patterns, which were obtained from the uniaxially oriented thin films of PET/PEN blends (PET/PEN ¼ 80/20, 50/50 and 20/80) prepared by applying the shear strain after keeping them in their molten state for 5 min, showed no crystalline reflections, in other words, 5 min is long enough for the transesterification reaction to occur, and accordingly in the resulting uniaxially oriented thin films of PET/PEN blends any crystalline structure was not formed.…”
Section: Resultsmentioning
confidence: 97%
“…Transcondensation was shown to occur in all the systems studied, except for those containing the LCP. Other studies also demonstrate the occurrence of transcondensation between PET and PEN, improving their miscibility [44]. Annealing temperature was found to influence transcondensation, but the blend composition appeared to have no effect.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Over many years, it has been agreed that this reaction is responsible for compatibility of blend components (Litmanovich et al, 2002;Ihm et al, 1996). However, Guo&Brittain, 1998, revealed that trans-esterification is not prerequisite to compatibility.…”
Section: Pair Of Pet With Polyethylenenaphtalate (Pen)mentioning
confidence: 99%
“…Analogous conclusions concerning the incompatibility of the physical blend and the decisive role of trans-esterification in the compatibility of PET and PEN were reported in (Ihm et al, 1996). If the degree of interchain exchange is greater than 50%, blends do not crystallize and a single glass transition point is observed only.…”
Section: Pair Of Pet With Polyethylenenaphtalate (Pen)mentioning
confidence: 99%